Soil and Water Loss Estimation Mathematical Models: A Review (International Journal of Geoscience, Engineering and Technology, 2024)
The erosion process is natural but has intensified in recent years due to anthropogenic activities, becoming a socio-environmental issue resulting from soil degradation. This process impacts various areas, and its measurement is a critical tool for adopting management strategies and conservation practices. Mathematical models can estimate soil losses under different environmental conditions. When integrated with GIS environments, these models significantly reduce execution and study costs, while generating valuable information, creating maps, and characterizing the environment. This study aimed to perform a systematic literature review on mathematical models for soil and water loss and to highlight some of their applications through the analysis of articles published in journals and indexed in electronic databases. Over the years, various models have been developed, and their use has proven essential for implementing conservation practices and restoring degraded areas. Due to the complexity of the process, it is crucial to consider the parameters available in each situation to select the most appropriate model.